Upgrade of an optical network unit in a 40 Gb/s time and wavelength-division multiplexed passive optical network using an upstream tunable colorless laser - Bindhaiq, Salem (2014)
A high data transmission rate is the main requirement for next-generation telecommunication networks. A design for a 40 Gb/s time and wavelength-division multiplexed passive optical network (TWDMPON) for next-generation passive optical network stage 2 is presented. The use of a modulated grating Y-branch (MG-Y) laser is proposed as an upstream tunable colorless laser source to upgrade the optical network unit. The electronically tuned MG-Y externally modulated laser with a 10 Gb/s modulation rate is applied to a TWDM-PON and presented across a 3.2-nm tuning range. The performance of the proposed laser is analyzed in terms of bit error rate, eye diagram, and optical signal-to-noise ratio. The proposed TWDM-PON achieved an aggregated data rate of 40 Gb/s along 40 km of bidirectional fiber at a 1:128 splitting ratio without amplification and dispersion compensation.